Comparison of transmission dynamics between Streptococcus uberis and Streptococcus agalactiae intramammary infections - Leelahapongsathon K. (2017)
© 2016 American Dairy Science Association. The objectives of study were to determine the transmission parameters (β), durations of infection, and basic reproductive numbers (R 0 ) of both Streptococcus agalactiae and Streptococcus uberis as pathogens causing mastitis outbreaks in dairy herds. A 10-mo longitudinal study was performed using 2 smallholder dairy herds with mastitis outbreaks caused by Strep. agalactiae and Strep. uberis, respectively. Both herds had poor mastitis control management and did not change their milking management during the entire study period. Quarter milk samples were collected at monthly intervals from all lactating animals in each herd for bacteriological identification. The durations of infection for Strep. uberis intramammary infection (IMI) and Strep. agalactiae IMI were examined using Kaplan-Meier survival curves, and the Kaplan-Meier survival functions for Strep. uberis IMI and Strep. agalactiae IMI were compared using log rank survival-test. The spread of Strep. uberis and Strep. agalactiae through the population was determined by transmission parameter, β, the probability per unit of time that one infectious quarter will infect another quarter, assuming that all other quarters are susceptible. For the Strep. uberis outbreak herd (31 cows), 56 new infections and 28 quarters with spontaneous cure were observed. For the Strep. agalactiae outbreak herd (19 cows), 26 new infections and 9 quarters with spontaneous cure were observed. The duration of infection for Strep. agalactiae (mean=270.84 d) was significantly longer than the duration of infection for Strep. uberis (mean=187.88 d). The transmission parameters (β) estimated (including 95% confidence interval) for Strep. uberis IMI and Strep. agalactiae IMI were 0.0155 (0.0035-0.0693) and 0.0068 (0.0008-0.0606), respectively. The R 0 (including 95% confidence interval) during the study were 2.91 (0.63-13.47) and 1.86 (0.21-16.61) for Strep. uberis IMI and Strep. agalactiae IMI, respectively. In conclusion, the transmission parameter and R 0 values were not different between both pathogens; however, the duration of infection for Strep. agalactiae was longer than Strep. uberis. These suggest that Strep. uberis may have a different transmission dynamic compared with Strep. agalactiae.